Study on the Effect of Phaseolus vulgaris Methanol Extract on Haloperidol and Tacrine Induced Parkinsonism - Kaur, Balvinder; Saxena, Jyoti (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Parkinson’s disease is neurodegenerative disease with no cure till now, there are treatments that can be explored to ease the symptoms of this disease, and using plant extract we explore the possibility of neutralizing the adverse symptoms and providing better quality of life to patients. Purpose: To demonstrate Anti-parkinson’s activity of Phaseolus vulgaris methanol pod extract by using behavioural models in Wister Albino rats. Materials and Methods: Animals were given Phaseolus vulgaris methanol extract (PVME) prior Haloperidol and Tacrine induced Parkinsonism. Results: Phaseolus vulgaris, family (Leguminosae) is a plant, well known for its Traditional and Ayurvedic application for the treatment of various diseases. In the present studies, Phaseolus vulgaris pods were used to evaluate its Antiparkinson’s activity in behavioral models in Albino rats. The models used here were Haloperidol-induced catalepsy and Tacrine-induced vacuous jaw movement. Phaseolus vulgaris methanol extract (PVME) of 200 and 400 mg/kg were given to rats prior to inducing Catalepsy. Haloperidol, an Antipsychotic drug that induces motor symptoms like Parkinson’s disease, PVME administration for 5 days, and on last day Haloperidol (1mg/kg i.p) was given and catalepsy was observed, it was seen that PVME reduces catalepsy score in a dose-dependent manner. Behavioral parameters also observed using Tacrine, which is an Anticholesterase drug induces chewing movements and orofacial bursts. The results were noted for a duration of 1 hr and found that PVME 400 mg/kg dose significantly reduces the movements and bursts as compared to 200 mg/kg dose. The given results were found close to the standard group (levodopa + carbidopa). Conclusion: The study conducted on Phaseolus vulgaris plant pod extract demonstrates the Neuroprotective activity of plant and its effectiveness to assess the symptoms of Parkinson’s disease. Antiparkinson’s effect of PVME shown to treat symptoms of motor dysfunction attributed to its tendency to reduce oxidative stress and having phenolic content.
Keywords: Phaseolus vulgaris; Haloperidol; Tacrine; Parkinson’s disease; Levodopa; Neuroprotective; Carbidopa; Oxidative stress